Video-tracked Anopheles arabiensis entry and exit behaviour at washed and damaged pyrethroid-treated bednets - Parker, Josephine; Kakilla, C.; Nelwin, K.; Kroner, C.; Logan, Rhiannon; Ismail, H. M.; Towers, C.; Manjurano, A.; Towers, D.; McCall, P. J. (Royal Society Open Science, 2024)
Insecticide-treated nets (ITNs) are the most effective method for malaria prevention in Africa. Using near-infrared video tracking in a laboratory environment, we recorded and assessed bednet entry and exit by a northern Tanzanian population of Anopheles arabiensis at a human-occupied untreated net and a PermaNet® 2.0 ITN. Both had 12 holes, each 10 cm in diameter, punctured at specific locations, and the ITN was washed 20 times to further simulate the wear and tear of ageing. Washing reduced the insecticide content of ITNs by 61%, which then showed similar rates to the untreated nets for net entry (39% entered untreated net and 41% entered ITN; p = 0.84) and exit (37% and 43%, respectively; p = 0.67). Regardless of treatment, approximately 40% of mosquitoes entered nets within 20 s of first appearing in the field of view and reached the volunteer’s skin within 5 s of entering the net. Mortality rates post-exposure were significantly higher (p = 0.048) at ITNs (26.6%; 95% CI 13.4%-39.7%) than at untreated controls (6.4%; 95% CI 1.8%-14.6%). The washed and aged ITN provided little additional personal protection for the sleeper over an untreated net. Simple adjustments to materials and design that could extend the effective lifespan of ITNs are discussed.
Veröffentlicht: 29 May 2024
Gesehen am 10.09.2024